Dicarboxylic acid monoester modified cellulose nanofiber

JP7629282B2Active Publication Date: 2025-02-13KRI INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2020134492
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-08-07
Publication Date
2025-02-13
Estimated Expiration
2040-08-07

AI Technical Summary

Benefits of technology

【0016】 本発明の製造方法は、反応溶液(解繊溶液)がプロトン性アミド系溶媒とジカルボン酸無水物を含む反応溶液であり、副反応が少なくセルロースへの浸透性と膨潤性に優れ、無触媒の状態でセルロースをジカルボン酸モノエステル化修飾して解繊したセルロースナノファイバーを製造することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007629282000003
    Figure 0007629282000003
  • Figure 0007629282000004
    Figure 0007629282000004
  • Figure 0007629282000005
    Figure 0007629282000005
Patent Text Reader

Abstract

To provide a method of producing dicarboxylic acid monoesterification modified cellulose nanofibers (CNFs) using a protic amide-based solvent, and an assembly of dicarboxylic acid monoesterification modified CNFs whose main constituent is single CNFs with fiber diameters of 3-10 nm.SOLUTION: A method of producing dicarboxylic acid monoesterification modified cellulose comprises infiltrating a reaction solution containing a protic amide-based solvent represented by a formula (1), R1-C(=O)-NH(R2), and a dicarboxylic anhydride into between fibrils of cellulose so as to subject hydroxy groups on cellulose fibril surfaces to esterification reaction resulting in chemical fibrillation. (In the formula, R1 and R2 each represent a proton or C1-3 alkyl group.)SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Provided are a method for producing cellulose nanofibers modified by dicarboxylic acid monoesterification using a reaction solution in a novel solvent, and cellulose nanofibers modified by dicarboxylic acid monoesterification of single cellulose nanofibers. [Background technology]

[0002] Cellulose fibers make up about 40% of plant cell walls and are the most abundant organic resource on earth. In addition to having excellent elasticity, strength, and dimensional stability, they are also environmentally friendly, making them highly anticipated as an alternative to petroleum-derived plastics.

[0003] Cellulose is a natural polymer in which β-glucose molecules are polymerized in a linear chain through glycosidic bonds. Cellulose fibers are formed through structural stages such as cellulose molecular chains, elementary fibrils (approximately 3-10 nm wide), microfibrils (20-50 nm wide), fibrils (several hundred nm wide), and lamellae. Depending on the production method, cellulose nanofibers include elementary fibril fibrils (single cellulose nanofibers or monofilaments) with a width of 3 to 10 nm, which are the most basic unit; cellulose microfibril bundles (cellulose nanofibers) with a width of 20 to 50 nm, which exist as basic units in cell walls by forming several loose bundles of these; and microfibrillated cellulose (MFC), in which microfibril bundles further combine into bundles of tens to hundreds of nm to form a spider web-like network. In other words, when cellulose fibers are broken down into microfibrils, they become the conventional concept of cellulose nanofibers (CNFs, hereinafter cellulose nanofibers may be abbreviated as "CNFs"), which are several tens of nm wide. When broken down further into elementary fibrils, they become single cellulose nanofibers (single CNFs), which are several nm wide.

[0004] Depending on the production method, cellulose nanofibers have been developed into unmodified CNF, acylated modified CNF, and anionic CNF such as dicarboxylic acid modified CNF. Regarding dicarboxylic acid modified CNF, a solventless method (Non-Patent Document 1) and a solvent method (Patent Documents 1 and 2) have been known so far.

[0005] However, in the solvent-free method, the dicarboxylic anhydride does not easily penetrate between the cellulose fibrils, so the degree of defibration of the obtained CNF and the uniformity of the distribution of the modification groups are low.In addition, because the method is performed without a catalyst and at high temperatures, not only dicarboxylic acid monoesters but also dicarboxylic acid diesters are formed, which may lead to cross-linking between fibrils.

[0006] On the other hand, Patent Documents 1 and 2, which use the solvent method, describe dicarboxylic acid-modified CNF, which is chemically defibrated by permeating and reacting cellulose with a defibration solution containing a catalyst and a dicarboxylic acid anhydride (claim 1) or a defibration solution containing a catalyst, a dicarboxylic acid anhydride, and an aprotic solvent (claim 3). However, as shown in Table 1 of the examples of Patent Document 1, in order to perform good defibration indicated by the degree of defibration marked with ⊚, a reaction time of 24 hours or more is required in both cases where a mixture of succinic anhydride or phthalic anhydride is used as a catalyst with pyridine, which also serves as a solvent (Examples 1 to 3), and where pyridine, a solvent (DMAc, DMSO, etc.), and a dicarboxylic acid such as succinic anhydride (Examples 4 to 6, 10) are used.

[0007] The solvents for the defibration liquid shown in Patent Documents 1 and 2 are aprotic solvents with a donor number of 25 or more, including pyridine, which is a solvent that also serves as a catalyst, and each has the following problems. Pyridine is a solvent with a low boiling point and high flammability, and is highly toxic and has a strong, distinctive odor, making it harmful to humans and the environment, and difficult to handle. When aprotic solvents other than pyridine are used in combination with a basic catalyst, side reactions occur with cellulose when heated, causing the cellulose and solvent to discolor, making it impossible to heat the solution and shortening the reaction time. In addition, aprotic solvents other than DMSO have the problem of low permeability to cellulose. Furthermore, in Patent Documents 1 and 2, single dicarboxylic acid-modified cellulose nanofibers were not obtained. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2017-082188 A [Patent Document 2] JP 2017-190437 A [Non-patent literature]

[0009] [Non-Patent Document 1] Chem.Soc.Rev.,2011,10,3941-3994 Summary of the Invention [Problem to be solved by the invention]

[0010] The present invention provides a method for producing dicarboxylic acid monoesterified modified cellulose nanofibers by reacting a dicarboxylic acid anhydride with cellulose in the absence of a catalyst, preferably with the addition of a base catalyst, using a protic amide solvent as the solvent. The present invention also provides an aggregate of cellulose nanofibers composed primarily of dicarboxylic acid monoester modified single cellulose nanofibers. [Means for solving the problem]

[0011] As a result of extensive investigations aimed at achieving the above object, the present inventors have completed the invention described below. [1] A method for producing dicarboxylic acid monoesterified modified cellulose, in which a reaction solution containing a dicarboxylic acid anhydride and a protic amide solvent represented by the following formula (1) is penetrated between cellulose fibrils to cause an esterification reaction of the hydroxyl groups on the surface of the cellulose fibrils, thereby chemically defibrating the cellulose fibrils. R1-C(=O)-NH(R2) (1) (In the formula, R1 and R2 represent a proton or an alkyl group having 1 to 3 carbon atoms. R1 and R2 may be the same or different.) [2] The method according to [1] above, wherein the protic amide solvent is at least one of formamide, methylformamide, acetamide, and N-methylacetamide. [3] The method according to [1] or [2] above, wherein the dicarboxylic acid anhydride is at least one of maleic anhydride, an aliphatic dicarboxylic acid anhydride having 4 to 8 carbon atoms, and phthalic anhydride. [4] The method according to any one of the above [1] to [3], wherein the reaction solution further contains a base catalyst. [5] A method for producing dicarboxylic acid monoester modified cellulose nanofibers, comprising a first step of producing a dicarboxylic acid monoester modified cellulose by any of the production methods described in [1] to [4] above, and a second step of dispersing the dicarboxylic acid monoester modified cellulose produced in the first step in water or an aqueous solution of a polar solvent at a concentration of 50% or less, and defibrating the cellulose into dicarboxylic acid monoester modified single cellulose nanofibers by electrostatic repulsion and shear force. [6] An aggregate of dicarboxylic acid monoester modified cellulose nanofibers having a fiber diameter of 3 to 100 nm, characterized in that the cellulose nanofibers constituting the aggregate have a cellulose Iβ crystal structure, have an average degree of substitution of dicarboxylic acid monoester groups of 0.1 to 1.0, and have a visible light transmittance of 65% or more in a 0.3 wt % aqueous dispersion of the aggregate. [7] An aggregate of dicarboxylic acid monoester modified cellulose nanofibers having a fiber diameter of 3 to 100 nm, characterized in that the cellulose nanofibers constituting the aggregate have a cellulose Iβ crystal structure and an average substitution degree of dicarboxylic acid monoester groups of 0.1 to 1.0, and the number content of single cellulose nanofibers constituting the aggregate and having a fiber diameter of 3 to 10 nm is 98% or more. [8] An aggregate of dicarboxylic acid monoesterified modified cellulose nanofibers according to [6] or [7], characterized in that the average fiber length of the single cellulose nanofibers constituting the aggregate is 200 nm or more and less than 1000 nm.

[0012] Here, the aggregate of cellulose nanofibers is a mixture containing single cellulose nanofibers with a fiber diameter of 3 to 10 nm and cellulose nanofibers with a fiber diameter of 10 to 100 nm. Preferably, it is a mixture containing single cellulose nanofibers with a fiber diameter of 3 to 10 nm and cellulose nanofibers with a fiber diameter of 10 to 50 nm. The form of the mixture is not particularly limited. It may be selected according to the application. For example, it may be in the form of a dispersion in water or an organic solvent, a paste, a gel, a dry state, or a state dispersed in a resin.

[0013] The average degree of substitution is the proportion of modified hydroxyl groups in cellulose, and more specifically, is the average value (average degree of substitution) of the number of modified hydroxyl groups (number of substituents) per repeating unit of cellulose.

[0014] The number content of the dicarboxylic acid monoester modified single cellulose nanofibers described in [7] above was determined by observing a sample sampled from the aggregate of the dicarboxylic acid monoester modified cellulose nanofibers using TEM images at a magnification of 400,000 or more, counting the number of large CNFs (crude CNFs) with a fiber diameter of more than 10 nm in randomly selected images, and confirming that the number of single cellulose nanofibers with a fiber diameter of 3 to 10 nm was 49 times or more that number.

[0015] The average fiber length of the dicarboxylic acid monoester modified single cellulose nanofibers was measured as follows. To measure the fiber length of single cellulose nanofibers with a fiber diameter of 3 to 10 nm, the CNF dispersion for observation was diluted as much as possible to reduce overlap of CNFs, and a TEM observation sample was prepared. Measurements were taken using TEM images at a magnification of 400,000 or more. If the CNF was curved, both ends of the fiber were found along the fiber curve, and the straight-line distance between each curve was measured and added to obtain the fiber length. Effect of the Invention

[0016] In the production method of the present invention, the reaction solution (defibration solution) contains a protic amide solvent and a dicarboxylic acid anhydride, and has few side reactions, excellent permeability to cellulose and swelling properties, and can produce defibrated cellulose nanofibers by modifying cellulose with dicarboxylic acid monoesterification in the absence of a catalyst.

[0017] According to the production method of the present invention, not only can side reactions be avoided, but also the reaction time can be significantly shortened, and the dicarboxylic acid monoesterification modification reaction can be carried out by heating without using a catalyst.

[0018] The reaction solution of the present invention penetrates between cellulose fibrils to modify the hydroxyl groups on the surface of the cellulose fibrils with dicarboxylic acid monoesterification, and then electrostatic repulsion and shear force are applied to produce an aggregate of cellulose nanofibers whose main component is single cellulose nanofibers modified with dicarboxylic acid monoesterification.

[0019] In the manufacturing method of the present invention, by adding a base catalyst to the reaction solution (defibration solution), the esterification reaction between the dicarboxylic acid anhydride and the hydroxyl groups of cellulose is promoted, making it possible to shorten the reaction time and lower the reaction temperature.

[0020] The cellulose nanofiber aggregate mainly composed of the dicarboxylic acid monoester modified single cellulose nanofiber of the present invention has high transparency because the average fiber diameter of the CNF is small and the distribution of fiber diameters is narrow. When the cellulose nanofiber is composited with a resin as a reinforcing material, the transparency of the resin can be ensured. Furthermore, despite the fiber length being less than 1 μm, the aspect ratio is 100 or more, so that both dispersibility and reinforcing effect can be achieved. [Brief description of the drawings]

[0021] [Figure 1] Photographs of 0.3% aqueous dispersions of dicarboxylic acid monoesterified modified CNF obtained in Example 1, Examples 3 to 7, Examples 9 and 10, and Comparative Example 1. [Diagram 2] IR spectra of dicarboxylic acid monoester modified CNF obtained in Example 1, Examples 3 to 7, and Example 10 [Diagram 3] UV spectra of 0.3% aqueous dispersions of dicarboxylic acid monoesterified modified CNF obtained in Example 1, Examples 3 to 7, Examples 9 and 10, and Comparative Example 1 DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] The method for producing dicarboxylic acid monoester-modified cellulose nanofibers of the present invention is characterized in that a reaction solution containing a dicarboxylic acid anhydride and the protic amide-based solvent of formula (1) is penetrated between cellulose fibrils, and the hydroxyl groups of the cellulose fibrils are modified by dicarboxylic acid monoesterification reaction to perform dicarboxylic acid monoester modification and chemical fiberization.

[0023] The cellulose used as the raw material in the present invention may be in the form of cellulose alone or in a mixed form containing non-cellulose components such as lignin and hemicellulose. Examples of cellulose in a pure form (or cellulose with a small content of non-cellulose components) include pulp (e.g., wood pulp, bamboo pulp, straw pulp, bagasse pulp, linter pulp, flax pulp, hemp pulp, paper mulberry pulp, mitsumata pulp, etc.), sea squirt cellulose, bacterial cellulose, cellulose powder, crystalline cellulose, etc. Examples of mixed forms of cellulose (cellulose compositions) include wood (e.g., conifers (pine, fir, spruce, hemlock, cedar, etc.), broad-leaved trees (beech, birch, poplar, maple, etc.)), herbaceous plants (hemp (hemp, flax, Manila hemp, ramie, etc.), straw, bagasse, Mitsumata, etc.), seed hair fibers (cotton linters, bombax cotton, kapok, etc.), bamboo, sugar cane, paper, etc.

[0024] These celluloses can be used alone or in combination of two or more. In the mixed form of cellulose, the ratio of non-cellulose components may be 90% by weight or less, for example, 1 to 90% by weight, preferably 3 to 80% by weight, and more preferably about 5 to 70% by weight. If the ratio of other components is too high, it may be difficult to produce dicarboxylic acid monoester modified CNF.

[0025] The cellulose preferably contains crystalline cellulose (particularly type I crystalline cellulose), or may be a combination of crystalline cellulose and non-crystalline cellulose (such as amorphous cellulose). The proportion of crystalline cellulose (particularly type I crystalline cellulose) may be 10% by weight or more based on the total cellulose, for example, 30 to 99% by weight, preferably 50 to 98.5% by weight, and more preferably about 60 to 98% by weight. If the proportion of crystalline cellulose is too low, the heat resistance and strength of the dicarboxylic acid monoester modified CNF may decrease.

[0026] Among these, wood pulp (e.g., softwood pulp, hardwood pulp, etc.), seed hair fiber pulp (e.g., cotton linter pulp), cellulose powder, etc. are commonly used because they are easy to modify and defibrate. The pulp may be mechanical pulp obtained by mechanically treating pulp material, but chemical pulp obtained by chemically treating pulp material is preferred because it has a low content of non-cellulose components.

[0027] The moisture content of cellulose (weight ratio of moisture to dry cellulose) may be 1% by weight or more, for example, about 1 to 100% by weight, preferably 2 to 80% by weight, and more preferably about 3 to 60% by weight (particularly 5 to 50% by weight). In the present invention, from the viewpoint of the permeability or swelling efficiency of the reaction solution, it is preferable that the cellulose contains moisture in such a range, and for example, in the case of commercially available cellulose pulp, the cellulose pulp may be used as it is without drying. If the moisture content is too low, there is a risk that the defibration property of the cellulose may decrease. Regarding the pretreatment of the cellulose raw material, it is preferable to crush the cellulose raw material (especially when pulp is used) into a size that can fit into the defibration reaction device or container by tearing or shredding it depending on the size of the defibration reaction device, and then subject it to the defibration reaction process.

[0028] The dicarboxylic acid anhydride includes aliphatic dicarboxylic acid anhydrides, alicyclic dicarboxylic acid anhydrides, and aromatic dicarboxylic acid anhydrides. Preferred dicarboxylic acid anhydrides are maleic anhydride, aliphatic dicarboxylic acid anhydrides having 4 to 8 carbon atoms, and phthalic anhydride. Preferred aliphatic dicarboxylic acid anhydrides having 4 to 8 carbon atoms include succinic anhydride, glutaric anhydride, adipic anhydride, pimelic anhydride, suberic anhydride, azelaic anhydride, and sebacic anhydride.

[0029] Further, preferred dicarboxylic anhydrides are succinic anhydride, maleic anhydride and glutaric anhydride, because these anhydrides are inexpensive and readily available commercially.

[0030] As the reaction solvent, a protic amide solvent represented by the following formula (1) is used. R1-C(=O)-NH(R2) (1) (In the formula, R1 and R2 represent a proton or an alkyl group having 1 to 3 carbon atoms. R1 and R2 may be the same or different.)

[0031] A preferred protic amide solvent has a dielectric constant of 45 or more at room temperature and an acceptor number of 20 or more. Examples include formamide (FA), N-methylformamide (MFA), N-ethylformamide, acetamide, N-methylacetamide, N-ethylacetamide, etc. Preferred are formamide, methylformamide, acetamide, and N-methylacetamide, and most preferred are formamide and methylformamide.

[0032] The solvent used in the production of modified cellulose nanofibers must be able to dissolve the reactant, and the four most important properties are the rate of penetration into cellulose, the degree of swelling of cellulose, and the ability to promote the modification reaction. These properties are thought to govern the fiber diameter and uniformity of the modified cellulose nanofibers. Protic amide solvents, particularly formamide, N-methylformamide, acetamide and N-methylacetamide, have both of these effects and are suitable for heating reactions due to their high solvent boiling points. In addition, protic amide solvents are preferred because they are believed to have a high effect of stabilizing anions by solvation. Furthermore, protic amide solvents differ from general protic polar solvents in that they have a low ability to donate or release protons from the solvent itself, and therefore competitive reactions are unlikely to occur.

[0033] As long as the reaction solution does not reduce the permeability of the cellulose or cause side reactions, it is also possible to add an aprotic solvent such as DMAc, DMF, NMP, DMSO, ketones such as acetone, or ethers such as THF. The ratio of the aprotic solvent added to the protic amide solvent is 50 wt% or less, preferably 35 wt% or less, and more preferably 30 wt% or less of the total solvent. If the content of the aprotic solvent exceeds this range, the permeability decreases and side reactions occur, which is undesirable.

[0034] The concentration of the dicarboxylic anhydride contained in the protic amide solvent may be appropriately adjusted depending on the type or reactivity of the anhydride, and the reaction conditions (temperature, time, pulp concentration, presence or absence of catalyst). For example, it is 1 to 50% by weight, more preferably 1.5 to 40% by weight, even more preferably 2 to 35% by weight, and most preferably 3 to 30% by weight. If the concentration is lower than this range, the reaction rate may decrease or the modification rate may decrease, which is not preferable. Conversely, if the concentration is higher than this range, it is not preferable because the dicarboxylic anhydride may not be completely dissolved or the permeability of the reaction solution between cellulose fibrils may decrease.

[0035] The weight ratio of cellulose to the reaction solution can be selected from the range of about 1 / 99 to 35 / 65 (former / latter), for example, about 1.2 / 98.8 to 30 / 70, preferably about 1.5 / 98.5 to 25 / 75, and more preferably about 2 / 98 to 20 / 80. If the ratio of cellulose is too low, the production efficiency of dicarboxylic acid monoester modified CNF will be low, and if it is too high, the reaction time will be long, so in either case, there is a risk of productivity decreasing. Furthermore, if the ratio of cellulose is too high, there is a risk of the uniformity of the size and modification rate of the obtained fine fibers decreasing.

[0036] A base catalyst may further be added to the reaction solution. The reaction solution preferably contains a base catalyst, since it can lower the reaction temperature and shorten the reaction time. The base catalyst is not particularly limited, but examples thereof include alkali metal carbonates such as sodium carbonate, potassium carbonate, and lithium carbonate, alkali metal hydrogen carbonates such as sodium hydrogen carbonate, alkyl metal acetates such as sodium acetate and potassium acetate, alkyl metal hydroxides, and amines. Among these, alkali metal carbonates and alkyl metal acetates are preferred, and sodium carbonate, potassium carbonate, lithium carbonate, sodium acetate, and potassium acetate are more preferred. On the other hand, alkyl metal hydroxides are highly basic, and may cause hydrolysis of dicarboxylic acid anhydrides, so their use has a low priority.

[0037] The concentration of the base catalyst in the reaction solution may be appropriately controlled depending on the type of dicarboxylic anhydride and the reaction temperature. For example, it is 0.01 to 10% by weight, preferably 0.05 to 5% by weight, more preferably 0.1 to 4% by weight. Most preferably, it is 0.2 to 3% by weight. If it is lower than this range, the catalytic action cannot be expected, which is not preferable. On the other hand, if it is higher than this range, it is not preferable because it may lead to decomposition of cellulose and dicarboxylic anhydride.

[0038] The method of modifying cellulose with dicarboxylic acid monoesterification can be carried out by penetrating a reaction solution between cellulose fibrils and chemically defibrating the hydroxyl groups on the surface of the cellulose fibrils through an esterification reaction. The method for chemical defibration is not particularly limited, and may be carried out by mixing the reaction solution with the raw cellulose.

[0039] The reaction solution is prepared by mixing a reaction solution containing a dicarboxylic anhydride and a protic amide solvent represented by the formula (1) above, and optionally adding a base catalyst to prepare the reaction solution. A typical method for preparing the reaction solution is to mix and stir the components to uniformly dissolve the other components in the solvent.

[0040] The reaction solution and the raw cellulose may be mixed by adding the raw cellulose to the reaction solution in the reaction vessel, or the reaction solution may be added to the raw cellulose in the reaction vessel. On a laboratory scale, a sample bottle or flask can be used as the reaction vessel. For scale-up, a reaction apparatus normally used in organic synthesis is recommended. When the cellulose concentration is high, a kneader such as a twin-screw extruder can also be used.

[0041] By stirring the mixture at a predetermined temperature for a predetermined time, the reaction solution is allowed to penetrate between the cellulose fibrils, and the hydroxyl groups on the surface of the cellulose fibrils are subjected to an esterification reaction to chemically disintegrate them, thereby obtaining a reaction product containing dicarboxylic acid monoesterified modified cellulose.

[0042] The reaction temperature is preferably 15°C to 250°C. If it is lower than 15°C, the reaction rate is low and the required reaction time is long, which is not preferable. If it is higher than 250°C, the cellulose or dicarboxylic anhydride may decompose, or the dicarboxylic monoester group may further dehydrate with the hydroxyl group of the cellulose, resulting in loss of anionicity, which is not preferable. The reaction temperature is more preferably 20°C to 200°C, and most preferably 23°C to 180°C.

[0043] The reaction can be carried out in an air atmosphere, but in the case of a reaction at high temperature, it is preferable to carry out the reaction under an inert gas in order to reduce the oxidation reaction of the reactant and cellulose. By carrying out the reaction under an inert gas, side reactions can be suppressed, which is preferable. Either nitrogen or argon gas can be used as the inert gas.

[0044] The stirring may be carried out by a method selected from various commonly used stirring methods. The shape of the cellulose modified by dicarboxylic acid monoesterification varies depending on the stirring method and the shear force. For example, when mild stirring such as a magnetic stirrer or mechanical stirring is used, the fiber diameter obtained is on the order of microns to tens of microns. Because the shape is large, it is easy to wash and can be easily washed by conventional filtration, pressure filtration, squeezing, etc. On the other hand, if a strong stirring method such as a paint shaker is used, most of the cellulose fibers after modification will have a nanoscale diameter. Therefore, the reaction method should be appropriately selected depending on the application and purpose.

[0045] The reaction time may be appropriately adjusted depending on the temperature, the dicarboxylic anhydride concentration, the catalyst concentration and the catalyst type. For example, in the case of reaction at room temperature without adding a catalyst, the reaction time is preferably 6 to 48 hours. The reaction time can be shortened by the addition of heat or a base catalyst. In the case of a heating reaction without adding a catalyst, the reaction time is preferably 1 hour to 24 hours. When a base catalyst is added, the reaction time can be shortened to 3 to 10 hours at room temperature, and to 30 minutes to 6 hours when heated.

[0046] A short reaction time is not preferred because the degree of modification may be low or the distribution of the dicarboxylic acid monoester groups may be non-uniform, which may result in a low transparency of the resulting dispersion of dicarboxylic acid monoester modified cellulose nanofibers, whereas a too long reaction time is not preferred because the dicarboxylic acid monoester groups may further react with other cellulose hydroxyl groups to produce dicarboxylic acid diester modified cellulose, which may inhibit defibration.

[0047] Next, the dicarboxylic acid monoesterified modified cellulose is separated and washed from the reaction solution containing the dicarboxylic acid monoesterified modified cellulose obtained by the reaction, thereby removing the protic amide solvent, dicarboxylic acid anhydride, dicarboxylic acid, base catalyst, etc. in the reaction solution, and the dicarboxylic acid monoesterified modified cellulose is recovered. The washing solvent is not particularly limited, but may be any solvent capable of dissolving each component of the reaction solution, and is preferably, for example, water, alcohol, or a mixture of water and alcohol. The washing method is not particularly limited, but possible methods include squeezing, pressure filtration, reduced pressure filtration, centrifugation, and precipitation.

[0048] Depending on the reaction conditions, it may be preferable to neutralize the reaction mixture with an alkali during washing. The alkali to be used for neutralization is not particularly limited, but examples thereof include alkali metal hydroxides such as sodium hydroxide, potassium hydroxide, and lithium hydroxide, alkali metal carbonates such as sodium carbonate, potassium carbonate, and lithium carbonate, and amine compounds.

[0049] The state of the recovered dicarboxylic acid monoesterified modified cellulose is not particularly limited. For example, after washing, it may be in a wet state still containing a protic solvent such as water, or in a dry state. Even if the recovered modified cellulose is dried, it will disperse again when water is added.

[0050] The shape of the recovered dicarboxylic acid monoesterified modified cellulose varies depending on the reaction conditions and stirring conditions during the modification reaction, but is usually fibrous with a fiber diameter of several μm to several tens of μm, fine fiber with a fiber diameter of several hundred nm to 1000 nm, or cellulose nanofiber with a fiber diameter of 3 nm to 100 nm. The faster the stirring speed, the more fiber is defibrated during the reaction, and the lower the content of fibers of the order of microns or more in the obtained anionic cellulose. However, if the stirring is too strong, the cellulose is decomposed to the nanoscale during the reaction, which reduces the water-releasing property during washing, increases the amount of washing solvent required for washing, or increases the washing time, which may lead to a decrease in production efficiency.

[0051] A dicarboxylic acid monoester modified cellulose nanofiber mainly composed of single CNF can be produced by a production method comprising the steps of: a first step of producing dicarboxylic acid monoester modified cellulose by any one of the production methods [1] to [4] above, in which a reaction solution containing a dicarboxylic acid anhydride and a protic amide solvent represented by the formula (1) is permeated between cellulose fibrils to modify the hydroxyl groups on the surface of the cellulose fibrils with dicarboxylic acid monoester; and a second step of dispersing the dicarboxylic acid monoester modified cellulose produced in the first step in an aqueous solution of water or a polar solvent containing 50% or less, and nano-sizing the cellulose by electrostatic repulsion and shear force.

[0052] In order to defibrate the modified cellulose into single CNF in the second step, the dicarboxylic acid monoester modified cellulose produced in the first step preferably has an average degree of substitution of dicarboxylic acid monoester groups of 0.10 or more, more preferably 0.12 or more, and even more preferably 0.15 or more. If the average degree of substitution is less than 0.10, the obtained anionic cellulose will have insufficient electrostatic repulsion in water, resulting in a low degree of defibration, and there is a risk of a high content of crude CNF with a fiber diameter exceeding 10 nm after defibration, which is not preferable.

[0053] In the second step, by combining electrostatic repulsion and mechanical defibration (shear force), cellulose can be nano-sized to 3 to 10 nm regardless of the shape of the fiber.In the second step, the dicarboxylic acid monoester modified cellulose produced in the first step is dispersed in water or an aqueous solution of 50% or less polar solvent, and defibrated by electrostatic repulsion and the application of mechanical or physical shear force. Due to the electrostatic repulsion effect, water (distilled water) is the most preferable dispersion solvent, but for the convenience of concentrating the CNF after nano-fibrillation, an aqueous solution of 50% or less of a polar solvent such as alcohol may also be used. Because the hydroxyl groups of CNF are replaced with anionic groups, it can be defibrated down to single CNFs with fiber diameters of 3 to 10 nm due to electrostatic repulsion in the dispersion solvent.

[0054] A preferred method for obtaining an aggregate of modified CNFs with fiber diameters of 3 to 100 nm, mainly composed of single CNFs with fiber diameters of 3 to 10 nm, is to adjust the solid content of the modified cellulose fibers in the dispersion solvent to approximately 0.1 to 0.8%, and then stir the mixture for 3 to 20 minutes using a stirring device such as a mixer or homogenizer.

[0055] If coarse fibers remain in the second step, they can be removed by filtering using a filter such as a nylon mesh.Further processing with a Clearmix or homogenizer can improve the degree of defibration or shorten the fiber length to the required range.

[0056] The first and second steps provide an aggregate of dicarboxylic acid monoester modified cellulose nanofibers having an average degree of substitution of dicarboxylic acid monoester groups of 0.1 to 1.0 and a number content of single cellulose nanofibers having fiber diameters of 3 to 10 nm constituting the aggregate of 98% or more.

[0057] The cellulose nanofibers constituting the aggregate of the dicarboxylic acid monoester modified cellulose nanofibers of the present invention preferably have a cellulose Iβ crystal structure, which is preferable because the aggregate of the dicarboxylic acid monoester modified cellulose nanofibers is strong and insoluble in general organic solvents.

[0058] The crystallinity of the cellulose nanofibers constituting the assembly of the present invention is 30% to 75%. If the crystallinity is higher than 75%, the content of nanofibers having a fiber diameter of 20 nm or more is high, and the transparency of the assembly is reduced, which is not preferable. Usually, the crystallinity of the cellulose nanofiber depends on the fiber diameter and reflects the fiber diameter. It is preferable to control the crystallinity to less than 70%, since it is possible to ensure that the content of single cellulose nanofibers having a fiber diameter of 3 to 10 in the assembly is 98% or more. On the other hand, if the crystallinity is 30% or less, the content of amorphous cellulose increases, which is not preferable, since there is a risk of a decrease in the reinforcing effect and thickening effect. The crystallinity is more preferably 35 to 69%, and most preferably 40 to 68%.

[0059] The number of hydroxyl groups modified with dicarboxylic acid monoester in the cellulose nanofibers constituting the assembly of the present invention (average degree of substitution) is preferably 0.1 to 1.0, more preferably 0.12 to 0.9, and most preferably 0.15 to 0.8. If it is lower than 0.1, the content of CNFs with fiber diameters of 10 nm or more increases, and the transparency of the single cellulose nanofiber assembly may decrease. On the other hand, an average degree of substitution of 1.0 or more is not preferable because it may significantly decrease the degree of crystallinity.

[0060] The visible light transmittance of a 0.3 wt % aqueous dispersion of the aggregate of the dicarboxylic acid monoesterified modified cellulose nanofibers of the present invention is 65% or more. If it is less than 65%, the transparency of the reinforced composite and dispersion is low, which is not preferable. If the visible light transmittance is 65% or more, it is possible to ensure that the content by number of single cellulose nanofibers having a fiber diameter of 3 to 10 nm is 98% or more. The visible light transmittance is more preferably 75% or more, and most preferably 80% or more.

[0061] The number content of single cellulose nanofibers having a fiber diameter of 3 to 10 nm constituting the aggregate of the present invention is 98% or more. If the number content of single cellulose nanofibers having a fiber diameter of 3 to 10 nm is lower than 98%, the transparency of the reinforced composite or dispersion liquid is low, which is not preferable.

[0062] The average fiber length of the single cellulose nanofibers having a fiber diameter of 3 to 10 nm that constitute the aggregate is 200 nm or more and less than 1000 nm. If it is shorter than this range, the reinforcing effect, thickening effect, and water retention effect are reduced, which is not preferable. On the other hand, if it is 1 μm or more, it is not preferable because it is prone to aggregation when compounded with a polymer and the reinforcing effect cannot be expressed. Furthermore, if the fiber length is too long, it is not preferable because the viscosity increases significantly when added to a paint or adhesive, and there is a risk that the paint or adhesive will lose its fluidity and processability. The average fiber length of the cellulose nanofibers constituting the aggregate is more preferably 250 nm to 900 nm, and most preferably 300 to 850 nm. EXAMPLES

[0063] The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples. Table 1 shows a list of the composition of the reaction solution and the reaction conditions in the examples and comparative examples. Details of the raw materials used are as follows, and the properties of the obtained modified cellulose nanofibers were measured as follows.

[0064] (Materials and solvents used) Cellulose pulp: Commercially available coniferous wood pulp (Georgia Pacific, product name: Fluff Pulp ARC48000GP) was used. It was cut into 1 cm cubes before use. Powdered cellulose: KC Flock W-100G manufactured by Nippon Paper Industries Co., Ltd., with an average degree of polymerization of 450, was used. Other reagents were purchased from Nacalai Tesque.

[0065] (Equipment used for defibration) Mixer: Panasonic MX-X701-T mixer. Clearmix: Clearmix CLM manufactured by M TECHNIQUE.

[0066] (IR analysis of cellulose nanofiber) The dicarboxylic acid monoesterification modification was confirmed by IR spectroscopy. The IR spectrum of the cellulose nanofiber was measured using a Fourier transform infrared spectrophotometer (FT-IR). The measurement was performed using a NICOLET MAGNA-IR760 Spectrometer manufactured by NICOLET, and analysis was performed in ATR mode.

[0067] (Quantitative determination of dicarboxylic acid monoester group modification rate of cellulose or CNF) The dicarboxylic acid monoester group modification rate of cellulose or CNF was expressed as the average substitution degree and was quantified by electrical conductivity titration. That is, 100 g of a 0.3% aqueous dispersion of cellulose modified by dicarboxylic acid monoesterification or CNF modified by dicarboxylic acid monoesterification was prepared, and 0.1 N hydrochloric acid aqueous solution was added thereto to adjust the pH to 2.5, and then 0.05 N sodium hydroxide aqueous solution was added dropwise until the pH reached 11, while recording the electrical conductivity value. The electrical conductivity and pH were plotted, and the number of moles of carboxylic acid groups Q was calculated from the amount of sodium hydroxide aqueous solution (a) consumed in the neutralization stage of the weak acid where the change in electrical conductivity was gradual, using the following formula. Q(mol)=a[ml]×0.05 / 1000 The average degree of substitution was calculated from the number of moles of the substituent, Q, and the molecular weight of anhydroglucan, the structural unit of cellulose (162). Average degree of substitution=162×Q / (100×0.3%-M×Q+18×Q) (In the formula, 100 is the amount of the aqueous dispersion of dicarboxylic acid monoester modified cellulose or dicarboxylic acid monoester modified CNF, M is the molecular weight of the dicarboxylic acid anhydride, and 18 is the molecular weight of water produced by dehydration through the reaction of the dicarboxylic acid anhydride with a hydroxyl group.)

[0068] (SEM observation) The shape of the dicarboxylic acid monoester modified cellulose nanofibers was observed using FE-SEM (JSM-6700F manufactured by JEOL Ltd., measurement conditions: 20 mA, 60 seconds).

[0069] (Preparation of TEM observation samples) The aggregate of dicarboxylic acid monoester modified cellulose nanofibers was diluted with water to 0.003%, then mixed with ionic liquid for electron microscopes (Hitachi High-Technologies HILEM IL1000) so that the final concentration was 0.0015% or less, and the mixture was dropped onto a carbon support film for TEM observation (Oken Shoji Super Hi-Res Carbon SHR-C075) and dried to prepare a sample for TEM observation. To enhance the image contrast, the above sample was subjected to electron staining (negative staining) using an electron microscope staining agent (Nissin EM EM Stainer) mainly composed of gadolinium acetate.

[0070] (TEM observation) The TEM observation sample was observed in a TEM bright field at an acceleration voltage of 120 kV using a field emission transmission electron microscope (FE-TEM) JEM-2100F manufactured by JEOL Ltd. CNFs with fiber diameters exceeding 10 nm were randomly found from the TEM photographs, and it was confirmed that there were more than 49 CNFs around it with fiber diameters of 10 nm or less. The average fiber diameter and average fiber length of single cellulose nanofibers with diameters of 3 to 10 nm were measured using TEM images at a magnification of 400,000 or more. More than 50 fibers were randomly selected from the TEM photograph, and the fiber diameter and length of each were measured. When the CNF was curved, both ends of the fiber were found along the fiber curvature, and the straight-line distance between each curvature was measured and added up to obtain the fiber length.

[0071] (Method of measuring crystallinity) The dispersion of the dicarboxylic acid monoester modified cellulose nanofiber was dried and the crystallinity was measured using powder X-ray crystal diffraction (XRD). The analysis was performed using an X-ray diffractometer (Ultima IV, manufactured by Rigaku Corporation). The measurement conditions are as follows: ·X-ray:Cu / 40kV / 40mA Scan speed: 10° / min Scanning range: 2θ=5~70° The crystallinity was calculated by the following formula (see Textile Res. J. 29:786-794, 1959). Crystallinity (%)=[(I200-IAM) / I200]×100 I200: Diffraction intensity at 2θ=22.6° IAM: Diffraction intensity of amorphous part at 2θ=18.5°

[0072] (Method of measuring thermal decomposition temperature) The aggregate of dicarboxylic acid monoesterified modified cellulose nanofibers was dried at 105°C for 2 hours, and its thermal decomposition behavior was analyzed using a thermogravimetric and differential thermal analyzer (STA7200, Hitachi High-Tech Science Corporation). The measurement conditions are as follows. The 5% weight loss temperature was measured and used as the thermal decomposition temperature. Atmosphere: Argon gas (flow rate 300 mL / min) Temperature range: 30~400℃ Heating rate: 10℃ / min

[0073] (Measurement of visible light transmittance) A 0.3% by weight aqueous dispersion of the dicarboxylic acid monoester modified cellulose nanofiber aggregate was prepared and measured using a UV-Vis spectrophotometer to measure the visible light transmittance at a wavelength of 589 nm (D-ray). The device used for the measurement was Shimadzu UV-3600, and the measurement wavelength range was 300 nm to 800 nm.

[0074] [Example 1] A mixture of 5 g of maleic anhydride and 45 g of formamide and 1.5 g of cellulose pulp were placed in a 100 ml round-bottom three-neck flask, a PTFE blade-type stirring rod was attached, and the mixture was stirred at room temperature for 30 minutes, then placed in a 60°C oil bath and stirred for 6 hours while argon gas was continuously flowing into the flask. After cooling, the reaction mixture was squeezed through a nylon mesh (T380) to remove the reaction solution, and the dicarboxylic acid monoesterified modified cellulose component and the reaction solution were collected. The recovered modified cellulose was dispersed in 150 g of distilled water and squeezed again to recover the dicarboxylic acid monoester modified cellulose component. After repeating dispersion and squeezing twice, the squeezed dicarboxylic acid monoester modified cellulose was dispersed in a solution of 0.4 g of sodium carbonate dissolved in 250 ml of water, squeezed again, and washed twice with 250 ml of distilled water to obtain maleic acid monoester modified cellulose. The washed maleic acid monoester modified cellulose and distilled water were combined to prepare 500 ml of dispersion, which was then placed in a mixer and stirred for 10 minutes to obtain an aqueous dispersion of maleic acid monoester modified cellulose nanofibers.

[0075] The appearance of the aqueous dispersion is shown in Figure 1. The maleic acid monoesterification modification was confirmed by IR spectroscopy (Figure 2). The absorption of the esterified bond was 1730 cm -1 The absorption of sodium terminal carboxylate is around 1600 cm -1 were found nearby. The maleic acid monoesterification modification rate (average substitution degree) of a 0.3% aqueous dispersion of the obtained maleic acid monoester modified CNF was confirmed to be 0.46 by electrical conductance titration method. The ultraviolet-visible transmittance spectrum chart of a 0.3% aqueous dispersion of the obtained maleic acid monoester modified CNF was measured, and the results are shown in Figure 3. The visible light transmittance was 67%. The crystallinity of the resulting aggregate of maleic acid monoester modified CNF was evaluated by XRD and found to be 69%, and the thermal decomposition temperature was 260°C by TG-DTA analysis. The resulting aggregate of maleic acid monoester modified CNF was observed by FE-SEM. When magnified up to 50,000 times, a nanofiber skeleton with a fiber diameter of about 10 nm or less was observed, but the exact fiber diameter and fiber length could not be clearly measured. Next, observations were made using a TEM. 50 cellulose nanofibers were randomly selected from the images obtained by TEM, and the fiber diameter and fiber length were measured. No fiber diameters exceeding 10 nm were observed, the number content of cellulose nanofibers between 3 and 10 nm was 98% or more, and the average fiber diameter of single CNF was 8 nm. It was also confirmed that the fiber lengths were distributed between 500 nm and 1000 nm, and the average fiber length was 945 nm. The evaluation results of the maleic acid monoester modified CNF obtained above are shown in Table 2.

[0076] [Example 2] Except for further treatment with Clearmix for 20 minutes after the mixer treatment, the same procedure was followed as in Example 1. That is, the same procedure and conditions as in Example 1 were followed except that the aqueous dispersion (0.3%) of maleic acid monoesterified modified cellulose nanofiber obtained by mixer treatment as in Example 1 was further treated with Clearmix CLM at a rotation speed of 18,000 rpm on a 100 ml scale for 20 minutes. The recovered maleic acid monoester modified CNF was evaluated in the same manner as in Example 1, and the results are shown in Table 2.

[0077] [Example 3] Except for changing the reaction temperature to room temperature (23°C) and the reaction time to 24 hours, maleic acid monoesterified modified CNF was prepared in the same manner as in Example 1. The evaluation results are shown in Table 2 and Figures 1, 2 and 3.

[0078] [Example 4] A succinic acid monoester modified CNF was prepared in the same manner as in Example 3, except that succinic anhydride was used instead of maleic anhydride as the modifying agent, N-methylformamide was used instead of formamide as the solvent, 0.75 g of sodium carbonate was added as a catalyst, and the reaction time was changed to 6 hours. The evaluation results are shown in Table 2 and Figures 1, 2 and 3.

[0079] [Example 5] Except for using formamide instead of N-methylformamide as the solvent, succinic acid monoester modified CNF was prepared in the same manner as in Example 4. The evaluation results are shown in Table 2 and Figures 1, 2 and 3.

[0080] [Example 6] Except for changing the reaction time from 6 hours to 4 hours, succinic acid monoester modified CNF was prepared in the same manner as in Example 5. The evaluation results are shown in Table 2 and Figures 1, 2 and 3.

[0081] [Example 7] Except for changing the amount of succinic anhydride added from 5 g to 2.5 g and the amount of formamide added from 45 g to 47.5 g, succinic acid monoester modified CNF was prepared in the same manner as in Example 6. The evaluation results are shown in Table 2 and Figures 1, 2 and 3.

[0082] [Example 8] Except for using glutaric anhydride instead of succinic anhydride, glutaric acid monoester modified CNF was prepared in the same manner as in Example 5. The evaluation results are shown in Table 2.

[0083] [Example 9] Except for using maleic anhydride instead of succinic anhydride and sodium bicarbonate instead of sodium carbonate, maleic acid monoester modified CNF was prepared in the same manner as in Example 5. The evaluation results are shown in Table 2 and Figures 1 and 3.

[0084] [Example 10] Except for using powdered cellulose instead of cellulose pulp, succinic acid monoester modified CNF was prepared in the same manner as in Example 5. The measurement results of the modification rate, crystallinity, visible light transmittance of the dispersion, etc. are shown in Table 2 and Figures 1, 2 and 3.

[0085] [Comparative Example 1] Except for using pyridine instead of formamide as the solvent and using succinic anhydride instead of maleic anhydride as the modifying agent, succinic acid monoester modified CNF was prepared in the same manner as in Example 3. The measurement results of the modification rate, crystallinity, and visible light transmittance of the dispersion are shown in Table 2 and Figures 1 and 3. The obtained aqueous dispersion of succinic acid monoester modified CNF was cloudy, and the visible light transmittance of the 0.3% aqueous dispersion was low at 38%. Although single CNF with fiber diameters of 3 to 10 nm were present, the presence of CNF with fiber diameters of 10 nm or more was noticeable.

[0086] [Comparative Example 2] Succinic acid modified cellulose nanofibers were synthesized in the same manner as in Examples 4 and 5, except that DMAc was used instead of N-methylformamide (Example 4) or formamide (Example 5) as the solvent. When sodium carbonate was added to a DMAc solution of succinic anhydride, the solution immediately changed color to red, then purple, and then squid ink. Pulp was added and stirred for 6 hours, and then washed and defibrated in the same manner as in Examples 4 and 5. The obtained aqueous dispersion of succinic acid monoester modified CNF was cloudy, and the visible light transmittance of the 0.3% aqueous dispersion was low at 9%. In addition, single CNF with a fiber diameter of 3 to 10 nm was hardly present.

[0087] [Comparative Example 3] Succinic acid-modified cellulose nanofibers were synthesized in the same manner as in Example 5, except that methanol was used instead of formamide as the solvent. After stirring for 6 hours, the pulp maintained its sheet shape and was not broken down even when defibrated in a mixer. After drying, the IR spectrum was measured, and no carbonyl groups were detected. This result demonstrated that methanol could hardly penetrate into the interior of the cellulose pulp, and no reaction occurred between cellulose and succinic anhydride.

[0088] [Comparative Example 4] Succinic acid-modified cellulose nanofibers were synthesized in the same manner as in Example 1, except that dimethyl sulfoxide (DMSO) was used instead of formamide as the solvent. 30 minutes after the start of the reaction, the reaction solution turned brown. The cellulose obtained after washing was yellow. The appearance did not change much even after defibrating with a mixer. These results indicate that the esterification reaction in DMSO is slow, and that side reactions occur, causing the cellulose fibers to become discolored and the fibers not to be defibrated.

[0089] Based on the results of the above examples and comparative examples, it was revealed that the reaction solution of the technology of the present application has excellent permeability into cellulose, and also has few side reactions, so that the obtained dicarboxylate-modified CNF does not discolor and the dispersion has high transparency. Furthermore, with or without the addition of a catalyst, no side reactions occurred even at room temperature or when heated, and dicarboxylate-modified cellulose nanofibers were obtained.

[0090] [Table 1] [Table 2] [Industrial Applicability]

[0091] The aggregate of the dicarboxylic acid monoester modified cellulose nanofibers of the present invention can be used as a resin reinforcing material, a composite material with inorganic particles, a coating agent, and can also be formed into a sheet or film for use. Furthermore, since it has functions such as emulsifying action (surfactant), thickening action, water retention or moisturizing action, it is expected to be applied in the fields of medical materials, pharmaceuticals, cosmetics, and food. Furthermore, since the aggregate of the dicarboxylic acid monoester modified cellulose nanofibers of the present invention has high transparency, it is particularly suitable as a reinforcing material for transparent resins.

Claims

1. A method for producing dicarboxylic acid monoesterified modified cellulose, comprising penetrating a reaction solution containing a dicarboxylic acid anhydride and a protic amide solvent represented by the following formula (1) between cellulose fibrils to cause an esterification reaction of hydroxyl groups on the surface of the cellulose fibrils, thereby chemically defibrating the cellulose fibrils. R1-C(=O)-NH(R2) (1) (In the formula, R1 and R2 represent a proton or an alkyl group having 1 to 3 carbon atoms. R1 and R2 may be the same or different.)

2. 2. The method according to claim 1, wherein the protic amide solvent is at least one of formamide, methylformamide, acetamide, and N-methylacetamide.

3. 3. The method according to claim 1, wherein the dicarboxylic acid anhydride is at least one of maleic anhydride, an aliphatic dicarboxylic acid anhydride having 4 to 8 carbon atoms, and phthalic anhydride.

4. The method according to any one of claims 1 to 3, wherein the reaction solution further contains a base catalyst.

5. A method for producing dicarboxylic acid monoesterified modified cellulose nanofibers, comprising: a first step of producing a dicarboxylic acid monoesterified modified cellulose by the production method according to any one of claims 1 to 4; and a second step of dispersing the dicarboxylic acid monoesterified modified cellulose produced in the first step in water or an aqueous solution of a polar solvent at a concentration of 50% or less, and defibrating the cellulose into dicarboxylic acid monoesterified modified single cellulose nanofibers by electrostatic repulsion and shear force.

Citation Information

Patent Citations

  • Method for producing stably dispersible cellulose nanofibers

    JP2015500354A

  • Modified cellulose fine fiber and method for producing the same

    JP2017082188A

  • Modified cellulose fine fiber and manufacturing method therefor

    JP2017190437A

  • Process for producing microfibrous cellulose, process for producing nonwoven fabric, microfibrous cellulose, slurry containing microfibrous cellulose, nonwoven fabric, and composite

    WO2013022025A1